Experimental Study on Capacitive Current Transfer Arc Suppression of Tree-line Discharge Fault in Distribution Network - Fuping ZHAO; Songhai FAN; Yiwei JI; Xin NING; Hao SHANG; Wenjun NING; Lihua ZHAO; Dehua ZENG (Zhongguo dianli)
The tree-line discharge faults of mountainous distribution networks may induce forest fires, so it is indispensable to study the low-cost and easy-to-control arc suppression measures for tree-line discharge faults in distribution networks. Based on a 10 kV distribution line experimental platform, the paper conducted an experimental study on the capacitive current transfer arc suppression for tree-line discharge faults in distribution networks. The experiments show that when the capacitive current transfer switch is closed, the arc or bright spot at the fault point disappears and the smoke dissipates, and the fault point current is reduced from several hundreds mA to about 20 mA, indicating that the method has a good arc suppression effect. The capacitive current transfer time is close to the intrinsic action time delay of the grounding transferring switch. Furthermore, different capacitive current and tree resistance are set to achieve effective arc suppression, and the transfer time is not significantly related to either tree resistance or capacitive current, demonstrating the universality of the capacitive current transfer arc suppression method.